REVITALISASI PERAN KARANG TARUNA SEBAGAI KOMUNITAS PENGGERAK ANTIMADAT DAN SEKS BEBAS (KOMPAS) REMAJA DI KAWASAN LOKALISASI DOLLY, SURABAYA - Sulistiawan, Dedik; Hakim, Lukman; Mahenda, Adelia Ratri; Bikatofani, Ryan Rizky; Ibad, Mursyidul (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2013)
Issues related to adolescent sexual deviation cases and drug abuse in Indonesia continues to increase. A total of 75 % of the 3.2 million drug users in Indonesia was a teenager . Of the 84 respondents who had experienced adolescent unwanted pregnancy , 60 % of whom have an abortion . The case with the teenagers in the Localization Dolly , Surabaya . The existence of Dolly contribute 71 % of the adolescent premarital sexual behavior in the vicinity. Meanwhile , youth are expected to play a role in movement and free sex antimadat in the region has not seen the real Dolly . This community service program aimed at restoring the role of youth organizations as an active community and helpless in society in movement and free sex antimadat promotive and preventive centered community -based approach , through the formation of peer educators . The method used is based on a theoretical framework Precede - PROCEED as a frame work development of health education programs . This program is proven to improve cognition in the Dolly teen population at risk as cases of sexual perversion and drug abuse . This activity produces an output in the form of the Youth Center as youth centers , triggering a re- active youth organizations in the target area . The key point of this program s success is the involvement of the subject s empowerment in decision-making that aims to arouse the internal motivation that makes the subject of empowerment as a necessity . Revitalization Role as Community Youth Activator Antimadat and Free Sex ( COMPASS ) Localization Region Youth Dolly , Surabaya is expected to be a best practice implementation of the empowerment of adolescent reproductive health , especially in the area of prostitution